Pengaruh Insentif dan Kepuasan Kerja Terhadap Kinerja Karyawan Bagian Marketing pada PT. Bank Negara Indonesia Kantor Cabang Tanjung Priok - Budhi Yuwono; Akbar Gladi Permana (JAMBIS : Jurnal Administrasi Bisnis, 2023)
This research was conducted to find out how big the influence of work environment on PT. Bank Negara Indonesia Kantor Cabang Tanjung Priokemployee performance.This research uses data and information retrieval method with questionnaire to employees of PT. Bank Negara Indonesia Kantor Cabang Tanjung Priokwith a sample of 70 employees. Sampling technique using Purposive Sampling. Each respondent answered the question as much as 24 by using Likert scale.The research method used in this research is quantitative associative where in this research there are 3 variable which represented independent variable that is Insentive (X1), Job Satisfaction (X2) and dependent variable that is employee performance (Y)From the results of research work Insentive positive or unidirectional and significant to employee performance, satisfaction of positive and unidirectional cooperation and significant to employee performance. Insentive and job satisfaction are the same as 75.2% performance on employee performance and 24.8% release by other factors that can not be in this research